Policy of Academic Revitalization through Information Technology for Quality Management Enhancement in Private Higher Education Institutions in Indonesia - Anuar Sanusi; Firmansyah Firmansyah; Muhammad Said Hasibuan; Nurfiana Nurfiana; Novi Herawadi S (LPPM Universitas Islam 45 Bekasi, 2024)
Private higher education in Indonesia faces challenges in improving educational quality to meet global demands. The policy of Academic Revitalization based on Information Technology (IT) emerges as a crucial strategy in addressing quality management changes. This research explores the implementation of this policy to enhance educational quality in private higher education institutions in Indonesia using seven variables. The research methodology involves a literature review and policy documentation analysis using Smart PLS. The research findings indicate that two variables were rejected due to being below the acceptance threshold. Five variables were accepted: Technology Alignment (3.258), Higher Education Quality Management (3.278), Moderating Effect 1 and 2 (both above 2.00), and the last variable, Revitalization of Academic Policies (2.614). However, challenges such as limited infrastructure, training needs, and appropriate policies remain significant issues to be addressed. In conclusion, the policy of Academic Revitalization based on IT provides a strong foundation for quality management changes in private higher education institutions in Indonesia. However, sustained commitment and significant investment are required to achieve optimal results.